Moderne schilderkunst II : Museum Boymans-van Beuningen Rotterdam : Aanwinsten 1962-1965 : Deel XVI N° 2. - Museum Boymans-van Beuningen, Rotterdam (Rotterdam : Museum Boijmans Van Beuningen, 1965)
Antes, Horst ; Bacon, Francis ; Bazaine, Jean ; Bissière, Roger ; van Bohemen, Kees ; De Chirico, Giorgio ; Constant ; Davie, Alan ; Engelman, Martin ; Ernst, Max ; Ficheroux, Mathieu ; Henkes, Dolf ; Hussem, Willem ; Jorn, Asger ; Kandinsky, Wassily ; Klee, Paul ; Magritte, René ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Pasmore, Victor ; Riopelle, Jean-Paul ; Saura, Antonio ; Segui, Antonio ; Soulages, Pierre ; de Staël, Nicolas ; Tilson, Joe ; Vasarely, Victor ; Vieira da Silva, Maria Elena ; Werkman, Hendrik Nicolaas
biog. per kunstenaar
Nederlands
boek